Problems of Learning the Qur’an in Early Childhood Education during the COVID-19 Pandemic - Aghnaita, Aghnaita; Norhikmah, Norhikmah (Al-Athfal: Jurnal Pendidikan Anak, 2022)
Purpose – The early learning of the Qur’an, infused with Islamic values, has been widely regarded as an effective tool in preserving the natural inclinations of children and nurturing their humanity. However, the ongoing COVID-19 pandemic has presented significant obstacles to Qur’an learning in Early Childhood Education (ECE) institutions. As such, this study seeks to offer a comprehensive description of the challenges faced by these institutions in delivering their teachings during this global health crisis.Design/methods/approach – The method used in this research is descriptive qualitative research. The location of this research was carried out at 4 ECE institutions. Namely: RA Al-Muslimun Nurul Islam, TKIT Asy-Syaamil Qur’anic Fullday School, Integrated Star Islamic Early Childhood Education, and RA Ulumul Qur’an Al Madani.Findings – The current COVID-19 pandemic has created significant challenges for learning the Qur’an in ECE. These issues can be categorized as internal and external factors. Internal factors relate to teachers’ difficulties when conducting practical learning activities outside the classroom. Meeting constraints, large class sizes, and limited time duration often result in an inability to deliver a complete learning experience. Externally, learning losses in early childhood have become apparent, with children experiencing behavioral changes. Not all parents are equipped to accompany their children in instilling Islamic values based on the Qur’an at home. This issue is compounded by parental objections to tuition fees, which creates financial challenges for institutions. Finally, offline learning has been the subject of criticism from the community, which indirectly affects the learning process.Research implications/limitations – This study used a qualitative method related to the problems of learning the Qur’an in ECE during the COVID-19 pandemic. Practical implications – The research presents significant implications for developing Al-Qur’an learning post-pandemic. It also provides valuable insights into formulating policies about Al-Qur’an learning during pandemics. Additionally, the study sheds light on the effectiveness of character building during the challenging times of the COVID-19 pandemic.Originality/value – Potential avenues for further investigation could include examining the effects of COVID-19 on the acquisition of Qur’anic knowledge during early childhood and its potential impacts on personality development. Such research could contribute to a deeper understanding of how the pandemic has influenced educational and psychological outcomes in this context. Paper type Research paper